2019
DOI: 10.3390/jcm8040538
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to a Medial Branch Block: MRI Analysis of the Lumbar Spine

Abstract: The aim of this study was to determine the association between radiologic spinal pathology and the response to medial branches block (MBB). This retrospective observational study compared 165 patients. A successful response was defined as ≥30% or a 2-point reduction in the numeric rating scale (NRS) compared with the baseline at the 1-month follow-up. The facet angle, facet angle difference, facet joint degeneration, disc height and spondylolisthesis grade were analyzed from an MRI at the L3 to S1 levels. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The predictor variables that were associated with achieving the SCB threshold at a significance level of p < 0.1 in the univariate analysis were entered into a multivariate logistic regression model, using a Backward Wald stepwise method. The threshold of p < 0.1 at the univariate stage was chosen to minimise the chance of eliminating potentially predictive variables at this stage [34]. Primary data analysis was conducted using logistic regression analysis and participants with a full data set (no missing outcome or predictor variables).…”
Section: Methodsmentioning
confidence: 99%
“…The predictor variables that were associated with achieving the SCB threshold at a significance level of p < 0.1 in the univariate analysis were entered into a multivariate logistic regression model, using a Backward Wald stepwise method. The threshold of p < 0.1 at the univariate stage was chosen to minimise the chance of eliminating potentially predictive variables at this stage [34]. Primary data analysis was conducted using logistic regression analysis and participants with a full data set (no missing outcome or predictor variables).…”
Section: Methodsmentioning
confidence: 99%
“…The structure, locating on the posterolateral region of the vertebral body and connecting the adjacent vertebral arch, is the facet joint, which constitutes the classic triple-joint complex with the intervertebral disc ( 28 ). In the current study, outcomes in consecutive patients suggested that increased FA limits functional recovery in the short term without impacting on long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming FA does not actually worsen surgical outcomes ( 31 ), a more convincing association was acknowledged. Due to the local fixation with pedicle screws, the altered facet joint stress accelerated disc degeneration, leading to an additional influence of disc height in predicting long-term outcomes ( 28 ). This explanation was also corroborated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this scale has been used as a means of surgical planning by identifying specific levels of pathology and disease severity, validity studies have reported conflicting results at best [ 16 , 17 , 18 ]. One retrospective observational study by Park et al included 165 patients, and demonstrated an association between facet angle difference (facet tropism) at L3–4 and disc height at L5–S1 to positive medial branch block response; however, the study’s power is limited and, thus, requires further investigation [ 19 ].…”
Section: Facet Arthropathymentioning
confidence: 99%